1989
DOI: 10.1172/jci114187
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying regional differences in lipolysis in human adipose tissue.

Abstract: Catecholamine-induced lipolysis was investigated in nonobese females and males. Isolated subcutaneous adipocytes were obtained from the abdominal and gluteal regions. The lipolytic effect of noradrenaline was four to fivefold more marked in abdominal adipocytes than in gluteal fat cells. This regional difference was more apparent in females than in males. No site differences were observed when lipolysis was stimulated with agents acting at different postreceptor levels. The beta-adrenergic lipolytic sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
140
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 230 publications
(158 citation statements)
references
References 29 publications
16
140
2
Order By: Relevance
“…It is generally accepted that visceral adipose tissue is more insulin resistant than subcutaneous adipose tissue [47,48]. Consequently, portal NEFA drainage may be more important than the systemic flux in the development of liver steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that visceral adipose tissue is more insulin resistant than subcutaneous adipose tissue [47,48]. Consequently, portal NEFA drainage may be more important than the systemic flux in the development of liver steatosis.…”
Section: Discussionmentioning
confidence: 99%
“…19 In human omental fat cells, the lipolytic activity is higher than in human subcutaneous fat cells, owing to the lower a 2 -adrenergic receptor ef®ciency and to site variations in the badrenoceptor subtypes. 20,21 In obese 22 or non-obese 23 subjects, the b-adrenergic lipolytic response is greater in subcutaneous abdominal than in gluteal adipocytes from both sexes. However, abdominal adipocytes of women showed lower a 2 -adrenergic antilipolytic sensitivity than did gluteal adipocytes, leading to a more pronounced regional difference in lipolysis in women than in men.…”
Section: Discussionmentioning
confidence: 99%
“…However, both states are characterized by increased FFA¯ux within the adipocyte and it has been suggested that UCP2 mRNA expression may be better correlated with fatty acid metabolism than with metabolic ef®-ciency. 34 Omental adipose tissue is known to have a higher rate of lipid turnover than subcutaneous adipose tissue, and this is related to a greater sensitivity to the lipolytic effects of catecholamines 35 and less sensitivity to the anti-lipolytic effects of insulin. 36,37 Thus, the greater UCP2 expression in human omental versus subcutaneous adipocytes would be consistent with a relationship between FFA¯ux and UCP2 expression.…”
Section: Discussionmentioning
confidence: 99%